2013
DOI: 10.3109/10428194.2013.788176
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of frail elderly patients with diffuse large B-cell lymphoma prospectively identified by Comprehensive Geriatric Assessment: results from a study of the Fondazione Italiana Linfomi

Abstract: In 2003 the Fondazione Italiana Linfomi (FIL) started a clinical research program for investigating initial treatment of frail elderly patients with diffuse large B-cell lymphoma (DLBCL) identified by Comprehensive Geriatric Assessment (CGA). From 2003 to 2006, 334 elderly patients underwent CGA assessment, and 99 patients were classified as frail. Frail patients had a median age of 78 years, stage III-IV disease in 62% and age-adjusted International Prognostic Index (aaIPI) of 2-3 in 53%. Treatment consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 21 publications
3
60
1
2
Order By: Relevance
“…Moreover, several studies as in the present have previously shown the utility of aaIPI in patients .60 years in the rituximab era. 46,47 It is interesting to note that the presence of the HLA-B44 supertype characterizes a group of patients who do not respond to rituximab in which novel strategies (ie, novel monoclonal antibodies) should be tested. On the other hand, the absence of the HLA-B44 supertype is capable of identifying an extremely good-risk prognostic subgroup that has a cure rate of .90% with current therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies as in the present have previously shown the utility of aaIPI in patients .60 years in the rituximab era. 46,47 It is interesting to note that the presence of the HLA-B44 supertype characterizes a group of patients who do not respond to rituximab in which novel strategies (ie, novel monoclonal antibodies) should be tested. On the other hand, the absence of the HLA-B44 supertype is capable of identifying an extremely good-risk prognostic subgroup that has a cure rate of .90% with current therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study of 476 DLBCL patients over 80 years found that R-CHOP also showed no OS benefit compared with nonanthracycline chemotherapy [Carson et al 2012]. An epirubicin-containing regimen, with lower anthracycline dose intensity but inclusion of rituximab, produced similar response rates, event-free survival, and OS in a randomized study of DLBCL patients aged 65 years or older [Merli et al 2012].…”
Section: Discussionmentioning
confidence: 99%
“…The number of comorbidities with a score of 3 or 4 and the sum of the score of each organ system represented comorbidity markers. CIRS-G was used in six studies [19][20][21][22]24,36]. However, the coding system was variable according to the authors.…”
Section: Comorbidity Assessment Methodsmentioning
confidence: 99%
“…Palliative treatment, including corticosteroids, radiation therapy or surgery alone, rituximab alone or no treatment at all, was considered in up to a third of patients in at least three studies [13,18,26] and half or more of the cohort in two other papers [22,24]. Dose reduction or number of cycles received was extremely variable and was erratically reported, and sometimes not reported at all.…”
Section: Treatmentmentioning
confidence: 99%